2021
DOI: 10.1097/tp.0000000000003490
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes After Liver Transplantation in Patients With Portopulmonary Hypertension

Abstract: Background. Portopulmonary hypertension (POPH) is the presence of pulmonary arterial (PA) hypertension in patients with portal hypertension and is associated with significant morbidity and mortality. In a cohort of POPH patients, we describe the clinical outcomes of POPH patients who underwent liver transplantation (LT). Methods. Retrospectively collected data from a prospectively assembled cohort of all consecutive POPH adults evaluated in 3 transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 29 publications
0
29
2
Order By: Relevance
“… 2 Long-term posttransplant survival rates are also overall similar to our recently reported survival rates for POPH patients at Mayo Clinic (n = 50) (1-y survival 72%, 3-y survival 63%, 5-y survival 60%). 15 Additionally, in contrast to older studies, acute perioperative cardiopulmonary mortality was low, and no patients died of POPH or right heart failure in the last decade. Our previously reported experience in patients without known POPH and an mPAP ≥ 35 mm Hg at the time of transplant has also been favorable with 96% (24/25) survival at 1-year posttransplant.…”
Section: Discussionmentioning
confidence: 93%
“… 2 Long-term posttransplant survival rates are also overall similar to our recently reported survival rates for POPH patients at Mayo Clinic (n = 50) (1-y survival 72%, 3-y survival 63%, 5-y survival 60%). 15 Additionally, in contrast to older studies, acute perioperative cardiopulmonary mortality was low, and no patients died of POPH or right heart failure in the last decade. Our previously reported experience in patients without known POPH and an mPAP ≥ 35 mm Hg at the time of transplant has also been favorable with 96% (24/25) survival at 1-year posttransplant.…”
Section: Discussionmentioning
confidence: 93%
“…An elevated PVR before LT was associated with worse survival rate (HR, 1.91), again emphasizing the importance of RV afterload on outcome. 51 By comparison, retrospective review of a large (637 patients) French cohort demonstrated 1-, 3-, and 5-year survival rates after LT of 84%, 69%, and 51%, respectively. 52 Most patients (90%) received PAH-specific therapy with improved NYHA functional class, 6MWD, and PVR.…”
Section: Special Populations and Topicsmentioning
confidence: 99%
“…Clinical outcomes for patients with POPH were examined in pooled data from all 3 Mayo Clinic LT centers. 51 Of 228 patients with POPH, 50 underwent LT. Significant hemodynamic improvement was observed after PAH-targeted therapy, and after LT, 21 (42%) patients were able to discontinue and to remain off PAH-targeted therapy.…”
Section: Special Populations and Topicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with POPH are suspected of having higher rates of mortality and graft failure following LT, but the precise impact of POPH and pretransplant hemodynamics on these important posttransplant outcomes is not well described. (19)(20)(21)(22) The purpose of this study is to better define the impact of POPH and pretransplant hemodynamics on posttransplant mortality and graft failure and identify hemodynamic thresholds that promote optimal outcomes in patients with POPH undergoing LT.…”
mentioning
confidence: 99%